The Impact of Cigarette Price Increases on Smoking Behaviour in Online Motorcycle Taxis in Jambi City - Yeni Mulyani; M. Ridwan; La Ode Reskiaddin (Sean Institute, 2024)
Background. The number of active smokers is increasing year by year around the world. There are 1.1 billion smokers worldwide who have caused the deaths of more than 200 million people over the past 30 years. Smoking causes an increasing public health burden globally. Objective. From this study will be obtained efforts in controlling smoking behaviour of online motorcycle taxi drivers in jambi city. Methods. This study uses a quantitative design with a cross-sectional approach. The sample used was 106 respondents. Which was taken by accidental sampling. Data collection using questionnaires by visiting online motorcycle taxi groups in 11 sub-districts of Jambi City by interviewing 11 sub-districts in Jambi city. Data analysis using chi-square test with univariate and bivariate analysis. Results. There is no impact of cigarette price increases on smoking behaviour in online ojek in Jambi City with a p-value of 0.016. With high cigarette prices, online ojek behaviour switches to cheaper brands. Conclusion. The increase in cigarette prices does not affect smoking behaviour in online motorcycle taxis in Jambi City.